Processo de certificação de frutos tropicais no polo de agricultura irrigada RN-CE e suas perspectivas - Lima, Francisco Jair Bezerra (Universidade Federal Rural do Semi-Árido, 2019)
With consumer awareness of the environment and concern for their health, the demand for healthy foods with fruits and that have been produced with agricultural practices with low impact on the environment is increasing. Thus, to ensure consumers that such requirements are being followed, companies use the certification seals. The objective of this work was to know the certification process, the difficulties of implementation and maintenance of the stamps, the stages of the process of implementation of the certification, verify the demand for certifications of the external market, as well as the trends both for the external market and for the internal market in relation to certification. To achieve these objectives, a qualitative case study was carried out. The case study was developed through interviews assisted by a pre-established questionnaire with open questions. The interviews were recorded and transcribed, later, being performed also by e-mail. The results showed that the certification process is time-consuming and expensive, which limits small producers to certifying their properties. Seals are mandatory requirements for medium and large producers to export their products. At the international level, there is a tendency for certifications focused on social and environmental issues to gain more space. At the national level, there is a tendency for the demand for certification by Brazilian consumers to increase, as there is increasing awareness of environmental issues and greater concern for food safety and health.
Monografia
Keywords: Certificação; Frutos tropicais; Exportação; Certification; Tropical fruits; Export; CIENCIAS AGRARIAS::AGRONOMIA